Is there benefit from the use of cochlear implants and hearing aids in cognition for older adults? A systematic review - Carasek, Natalia; Lamounier, Pauliana; Maldi, Isabela Gomes; Bernardes, Marina Nahas Dafico; Ramos, Hugo Valter Lisboa; Costa, Claudiney Cândido; Bahmad, Fayez (Frontiers in Epidemiology, 2022)
Objectives: To assess whether Hearing Aids (HA) and Cochlear Implants (CI) bring benefits to cognition or mitigate cognitive decline in older adults. Methods: Systematic Literature Review registered on the International Prospective Register of Systematic Reviews (PROSPERO) and based on the criteria recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The Population, Intervention, Comparison, Outcome and Study type (PICOS) strategy was used to define eligibility. Studies that met the criteria were included in the qualitative synthesis. We assessed the risk of bias through the Joanna Briggs Institute's Critical Appraisal Checklists. Results: A total of 3,239 articles, found in eight databases, addressed the relationship between HA, CI and cognition. We selected 30 experimental articles reporting measures of cognitive outcome for older adults to include in the qualitative analysis. Of those, 23 studies reported a significant improvement in outcome and 7 reported no significant change. Conclusions: This Systematic Review indicates that CI and HA can bring benefits to cognition in older adults.